Design and Implementation of Current Mode Controlled Single Output Two Switch Forward Converter for Railway Applications - Dr. V. SEKHAR; Sanapala Nageshwar Rao (Utilitas Mathematica, 2024)
This paper outlines the design and implementation of a high-frequency converter., miniaturized, single-output converter tailored for railway applications. The design employs a two-switch forward converter topology, ensuring both compactness and high efficiency. The proposed converter achieves enhanced line, load, and cross-regulation through the integration of post-regulators. The converter operates at a switching frequency of 110 kHz and utilizes the NCP1252A PWM controller to manage the modulation process. A separate output winding (Bias) is employed for feedback in the converter’s control loop. Current mode control is implemented by comparing the input current with the bias winding’s output, which modulates the pulse width generated by the PWM circuit. The converter’s performance is validated through an experimental setup, achieving a single output with a target efficiency of 90%. The two-switch forward converter design incorporates essential components such as a power transformer, electromagnetic interference/management circuit (EMI/MC), inrush current-limiting circuit, and protection mechanisms for both under-voltage and over-current conditions. These features contribute to the converter's robust performance and suitability for demanding railway applications, where reliability, efficiency, and compactness are of paramount importance.